The effects of diet and mating system on reproductive (and post‐reproductive) life span in a freshwater snail. Issue 23 (16th November 2018) - Auld, Josh R.
Abstract: The length of the reproductive life span, along with the number/frequency/magnitude of reproductive events, quantifies an individual's potential contribution to the next generation. By examining reproductive life span, and distinguishing it from somatic life span, we gain insight into critical aspects of an individual's potential fitness as well as reproductive and somatic senescence. Additionally, differentiating somatic and reproductive life spans can provide insight into the existence of a post‐reproductive period and factors that shape its duration. Given the known importance of diet and mating system on resource allocation, I reared individual freshwater snails ( Physa acuta ) from 22 full‐sib families under a 2 × 2 factorial design that crossed mate availability (available [outcrossing] or not [selfing]) and diet (Spirulina or lettuce) and quantified aspects of the entire life history enabling me to distinguish reproductive and somatic life spans, determine the total number of reproductive events, and evaluate how the reproductive rate changes with age. Overall, mated snails experienced shorter reproductive and somatic life spans; a diet of Spirulina also shortened both reproductive and somatic life spans. A post‐reproductive period existed in all conditions; its duration was proportional to somatic but not reproductive life span. I evaluate several hypotheses for the existence and duration of the post‐reproductive period, including a novel hypothesis that the post‐reproductive period may result from an increase in reproductive interval with age. I conclude that the post‐reproductive period may be indicative of a randomly timed death occurring as the interval between reproductive events continues to increase. As such, a "post‐reproductive" period can be viewed as a by‐product of a situation where reproductive senescence outpaces somatic senescence. Abstract : This is an experimental evaluation of reproductive and post‐reproductive life span in a freshwater snail, exploring the effects of diet and mating system on fundamental aspects of the life history. Snails reared on a higher quality diet or allowed access to a mating partner suffered a reduced reproductive life span. A post‐reproductive period exists under all conditions and its existence is discussed.